2017
DOI: 10.1148/radiol.2017170103
|View full text |Cite
|
Sign up to set email alerts
|

Needlestick Injuries in Interventional Radiology Are Common and Underreported

Abstract: Purpose To determine the prevalence of and risk factors for needlesticks in interventional radiology physicians, as well as the attitudes, behaviors, and conditions that promote or interfere with reporting of these injuries. Materials and Methods A total of 3889 interventional radiologists from academic and private practice in the United States were surveyed by emailing all interventional radiologist members of the Society of Interventional Radiology, including attending-level physicians and trainees (April-Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 22 publications
3
18
2
Order By: Relevance
“…The nonreporting rates of 32% (NSIs) and 36% (MCEs) from our study are slightly lower than the mean BBFE nonreporting rate of 41% (range, 29% to 98%) found in our literature review, 3,6‐9,12‐21,26‐31 which may reflect our study’s low response rate, variation in response rates by role, recall bias, or participation bias (if staff members with exposures were more or less inclined to participate). The results of our study and others suggest that reported BBFE data underestimate true incidence.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…The nonreporting rates of 32% (NSIs) and 36% (MCEs) from our study are slightly lower than the mean BBFE nonreporting rate of 41% (range, 29% to 98%) found in our literature review, 3,6‐9,12‐21,26‐31 which may reflect our study’s low response rate, variation in response rates by role, recall bias, or participation bias (if staff members with exposures were more or less inclined to participate). The results of our study and others suggest that reported BBFE data underestimate true incidence.…”
Section: Discussioncontrasting
confidence: 80%
“…Reports of never having received NSI‐prevention education from 27% of participants is puzzling because all hospital clinical personnel are required to complete annual online education modules for NSI prevention at the hospital where the data were collected. The reasons that respondents gave for not reporting an NSI that we also found in the literature included a lack of knowledge of reporting procedures 8,14,17,18,21,27‐29,30 and requirements, 3,13,15,17 stigma or shame, 8,12‐15,17,21,26‐30 and a belief that their own antibody status 8 or that personal protective equipment 9 prevented them from acquiring a bloodborne pathogen. …”
Section: Discussionmentioning
confidence: 84%
“…Staff working in procedure areas are at risk for needlestick injuries and exposure to contagious body fluids. Needlestick injuries are common among interventional radiologists, 91% of whom reported having at least one needlestick injury and 31% of whom reported having a needlestick injury involving a human immunodeficiency virus-positive patient (54). As most needle injuries result from recapping needles, preventative measures need to include raising awareness regarding and minimizing this practice.…”
Section: Exposure To Contagious Body Fluidsmentioning
confidence: 99%
“…In addition, good quality studies use a blind method for filling their questionnaires to minimize the rate of denial because of stigma. In a recent study in the US in which data were collected data by email, 91% of interventional radiologists had sustained NSIs, and only 66% of the injuries were reported (Deipolyi, Prabhakar, Naidu, & Oklu, ).…”
mentioning
confidence: 99%
“…The common reasons for NSI occurrence for nurses seem to be rushing, fatigue, lack of skill, stuck by others, and carelessness/accidents (Hasak, Novak, Patterson, & Mackinnon, ). Common reasons for not reporting NSIs may be a belief in low utility of reporting, long reporting processes, belief that the needle was not contaminated, and associated stigma (Deipolyi et al, ). The rate of these injuries is higher in healthcare workers in training and medical sciences students, compared to other groups of healthcare workers (Prüss‐Üstün, Rapiti, & Hutin, ).…”
mentioning
confidence: 99%